PENGARUH VOLATILITAS NILAI TUKAR RUPIAH, HARGA MINYAK MENTAH, DAN HARGA BATU BARA GLOBAL TERHADAP RETURN SAHAM DI BURSA EFEK INDONESIA DENGAN VOLATILITAS RETURN SAHAM SEBAGAI MEDIATOR - Bintang Firdaus; Mokhamad Anwar (Universitas Muhammadiyah Bengkulu, 2026)
This study aims to analyze the effect of Rupiah exchange rate volatility against the US dollar, global crude oil prices, and global coal prices on stock returns on the Indonesia Stock Exchange (IDX), with stock return volatility as a mediating variable. The research method used is a quantitative approach with an explanatory-causal design using daily time series secondary data from January 1, 2022, to December 30, 2025, obtained from Trading Economics. The analysis was conducted through stationarity tests, ARCH Effect tests, volatility estimation using the GJR-GARCH and EGARCH models, and mediation tests using the Two-Step Volatility Mediation approach. The results show that Rupiah exchange rate volatility has a positive and significant effect on stock return volatility, while global crude oil and coal price volatility has a negative and significant effect on stock return volatility. At the mediation stage, stock return volatility proved to be a significant intermediary variable in transmitting the influence of exchange rate volatility, crude oil prices, and coal prices on stock returns, while the direct effect of the three macroeconomic variables on stock returns became insignificant after the mediator was included in the model. The conclusion of this study shows that stock return volatility acts as the main transmission mechanism that bridges the influence of macroeconomic risk on stock returns on the Indonesia Stock Exchange, so that market volatility factors need to be a primary concern for investors and policymakers in facing global economic dynamics. Keywords: Exchange Rate Volatility, Crude Oil Prices, Global Coal Prices, Stock Returns, Stock Return Volatility